2000
DOI: 10.1007/s004670050048
|View full text |Cite
|
Sign up to set email alerts
|

The stressed neonatal kidney: from pathophysiology to clinical management of neonatal vasomotor nephropathy

Abstract: The healthy term, and particularly the premature infant, is born with a very low glomerular filtration rate (GFR), controlled by a delicate balance of intrarenal vasoconstrictor and vasodilator forces. Vasoactive disturbances can easily further reduce the already low GFR. The newborn infant is thus prone to develop vasomotor nephropathy (VMNP) or acute renal failure (ARF). The main causes for ARF at this young age are prerenal mechanisms, and include hypotension, hypovolemia, hypoxemia perinatal asphyxia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(131 citation statements)
references
References 122 publications
11
116
3
1
Order By: Relevance
“…These results are consistent with the observations reported for hypoxemia alone. They strengthen the notion of a vasomotor origin of the hypoxemia-induced insult on the immature kidney previously reported by our group [2][3][4][5][6] and suggest a role for IGF-1 deficiency in this complex phenomenon. In anesthetized adult rats given IGF-1, Baumann et al reported an increase in GFR, renal plasma flow and diuresis by 35%, 100% and 300%, respectively, whilst RVR decreased by 50%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with the observations reported for hypoxemia alone. They strengthen the notion of a vasomotor origin of the hypoxemia-induced insult on the immature kidney previously reported by our group [2][3][4][5][6] and suggest a role for IGF-1 deficiency in this complex phenomenon. In anesthetized adult rats given IGF-1, Baumann et al reported an increase in GFR, renal plasma flow and diuresis by 35%, 100% and 300%, respectively, whilst RVR decreased by 50%.…”
Section: Discussionsupporting
confidence: 91%
“…These results confirm that the renal microvasculature in the neonatal period is sensitive to exogenous IGF-1, even in pathogenic circumstances. Combined with the high survival rate seen with IGF-1, these results could be of clinical importance, as neonatal mortality and morbidity rates due to ARF remain very high [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, in sick preterm infants, many clinical conditions inducing hypotension, hypovolemia and hypoxemia and the use of nephrotoxic drugs may lead to further reduction of GFR. 9 In particular, nonsteroidal anti-inflammatory drugs (NSAID) that are given for treatment of patent ductus arteriosus (PDA) have been reported to impair renal perfusion 10 and the immature kidney is regarded as especially sensitive to NSAID renal effects. However, hemodynamically significant PDA (hsPDA) itself can be associated with poor renal perfusion and we could speculate that the NSAID renal effects may be exacerbated by a low GFR preceding NSAID administration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Glomerular function shows a progression directly correlated to gestational age (GA) and postnatal age in preterm infants. 4 In infants with very low GA, due to decreased glomerular filtration rate (GFR), normalization of serum creatinine values may be prolonged during recovery from acute renal failure (ARF).…”
Section: Introductionmentioning
confidence: 99%